(untitled) (World Economics and Finance Bulletin, 2024)
The study aimed to find out the role of creative leadership In building the ethical behavior of human resources according to a group of employees’ opinions in the Directorate of Education of Babylon, Where the descriptive analytical method was used for this research Mainly based on the questionnaire as the main tool for collecting data and information The research is based on a set of statistical tools to be processed According to the tests that achieve the purpose of the study Arithmetic mean, standard deviation, frequencies and percentages, Cronbach alpha test, multiple regression analysis. The questionnaire was distributed to the research community with (374) questionnaires The research community consisted of education departments spread in the province of Babylon, The sample of the study included its employees , The sampling unit was taken using the simple random sampling method. The study reached several conclusions, the most important of which are: That the creative leadership variable supports and enhances the ethical behavior of human resources, The study presented a set of recommendations, the most important of which was: Further strengthening the role of the creative leadership of the Directorate of Education of Babel And its connection with the value system and the endeavor to apply codes of ethics that will contribute to the promotion of ethical behavior and reduce and eliminate unethical behavior within their organizations This is what His Eminence, Grand Ayatollah Al-Sayyid Al-Sistani (may his legacy last).